A multiethnic whole genome sequencing study to identify novel loci for bone mineral density. Issue 7 (21st October 2021) - Greenbaum, Jonathan; Su, Kuan-Jui; Zhang, Xiao; Liu, Yong; Liu, Anqi; Zhao, Lan-Juan; Luo, Zhe; Tian, Qing; Shen, Hui; Deng, Hong-Wen
Abstract: At present, there have only been a few DNA sequencing-based studies to explore the genetic determinants of bone mineral density (BMD). We carried out the largest whole genome sequencing analysis to date for femoral neck and spine BMD ( n  = 4981), with one of the highest average sequencing depths implemented thus far at 22×, in a multiethnic sample (58% Caucasian and 42% African American) from the Louisiana Osteoporosis Study (LOS). The LOS samples were combined with summary statistics from the GEFOS consortium and several independent samples of various ethnicities to perform GWAS meta-analysis ( n  = 44 506). We identified 31 and 30 genomic risk loci for femoral neck and spine BMD, respectively. The findings substantiate many previously reported susceptibility loci (e.g. WNT16 and ESR1 ) and reveal several others that are either novel or have not been widely replicated in GWAS for BMD, including two for femoral neck ( IGF2 and ZNF423 ) and one for spine ( SIPA1 ). Although we were not able to uncover ethnicity specific differences in the genetic determinants of BMD, we did identify several loci which demonstrated sex-specific associations, including two for women ( PDE4D and PIGN ) and three for men ( TRAF3IP2, NFIB and LYSMD4 ). Gene-based rare variant association testing detected MAML2, a regulator of the Notch signaling pathway, which has not previously been suggested, for association with spine BMD. The findings provide novel insights into the pathophysiological mechanisms of osteoporosis.